Saltmarsh flies of the genus Scorpiurus Parent from New Zealand (Insecta: Diptera: Dolichopodidae) - Masunaga, Kazuhiro (Zootaxa, 2017)
The saltmarsh-inhabiting fly genus Scorpiurus Parent, 1933 is revised. Contrary to the consensus of previous literature, it seems to be endemic to New Zealand. Two species are recognized: Scorpiurus thorpei sp. nov. described herein, and its previously known congener, S. aenescens Parent, 1933, which is redescribed.